FACULTY PERCEPTIONS AND BARRIERS IN INTERDISCIPLINARY CURRICULUM IMPLEMENTATION: A QUANTITATIVE STUDY (Contemporary Journal of Social Science Review, 2025)
This paper explores faculty members' perceptions and barriers regarding the implementation of an interdisciplinary curriculum at the higher education level. The study aimed to assess faculty members' views on incorporating interdisciplinary approaches into the existing curriculum and identify the perceived barriers to implementation. A quantitative research design was used, with data collected through a structured questionnaire administered to faculty members at the International Islamic University Islamabad, National University of Modern Languages (NUML) Islamabad, and Arid University Rawalpindi. A random sampling technique was applied, achieving a 50% (27 teachers) response rate. Results indicated that faculty generally supported interdisciplinary approaches, with positive perceptions of curriculum integration; however, significant barriers, including administrative challenges, a lack of faculty training, and insufficient resources, were also identified. Based on these findings, it is recommended that universities invest in faculty development, provide adequate resources, and create platforms for cross-departmental collaboration to enhance interdisciplinary education.